Procedural outcomes of deep brain stimulation (DBS) surgery in rural and urban patient population settings. (February 2020) - Fana, Michael; Everett, Gregory; Fagan, Thomas; Mazzella, Megan; Zahedi, Sulmaz; Clements, John M.
Highlights: Urban patients more often non-routinely discharged with higher costs versus rural. Urban patients predicted to have 70% lower odds of routine discharge versus rural. Major loss of function before surgery shows 81% lower odds of routine discharge. Severe illness and urban patients have longer hospital stays and higher costs. Abstract: Presently, disparities exist between race, sex, socioeconomic status, hospitals, income, comorbidities, and insurance profiles of patients undergoing DBS surgery. Here, we aim to highlight several variables and their predictive powers of DBS surgery outcomes as measured by discharge location, length of hospital stays, and total hospital charges. A retrospective cohort study using discharge data from NIS and HCUP for analyses and regression model statistics is performed. Comparative analyses demonstrate urban patients were more often non-routinely discharged, possessed private insurance, and accrued greater hospital costs compared to rural patients. Moreover, regression analyses predicts urban patients have 70% lower odds of routine discharge while those with a major loss of function prior to surgery also have 81% lower odds of routine discharge compared to those with minor loss of function. Ultimately, our study found urban patients or patients with major illnesses have higher hospital charges, longer hospitalization, and more often non-routinely discharged.